Searching for large-scale structures around high-redshift radio galaxies with Herschel - Rigby, E.E.; Hatch, Nina A.; Rottgering, H.J.A.; Sibthorpe, B.; Chiang, Y.K.; Overzier, R.; Herbonnet, R.; Borgani, S.; Clements, D.L.; Dannerbauer, H.; De Breuck, C.; De Lucia, G.; et al. (Oxford University Press, 2014)
This paper presents the first results of a far-infrared search for protocluster-associated galaxy overdensities using the Spectral and Photometric Imaging REciever (SPIRE) instrument on-board the Herschel Space Observatory. Large (∼400 arcmin2) fields surrounding 26 powerful high-redshift radio galaxies (2.0 < z < 4.1; L500 MHz > 1028.5 WHz−1) are mapped at 250, 350 and 500 μm to give a unique wide-field sample. On average, the fields have a higher than expected, compared to blank fields, surface density of 500 μm sources within 6 comoving Mpc of the radio galaxy. The analysis is then restricted to potential protocluster members only, which are identified using a far-infrared colour selection; this reveals significant overdensities of galaxies in two fields, neither of which are previously known protoclusters. The probability of finding two overdensities of this size by chance, given the number of fields observed, is 5 × 10−4. Overdensities here exist around radio galaxies with L500 MHz ≳ 1029 WHz−1 and z < 3. The radial extent of the average far-infrared overdensity is found to be ∼6 comoving Mpc. Comparison with predictions from numerical simulations shows that the overdensities are consistent with having masses >1014 M⊙. However, the large uncertainty in the redshift estimation means that it is possible that these far-infrared overdensities consist of several structures across the redshift range searched.